Deformation mechanisms of dual-textured Mg-6.5Zn alloy with limited tension-compression yield asymmetry. (15th April 2023) - Yang, Biaobiao; Wang, Jun; Li, Yunping; Barnett, Matthew; LLorca, Javier
Abstract: A dual-textured wrought Mg-6.5 Zn (wt.%) alloy with limited yield asymmetry (compressive yield strength / tensile yield strength: 0.90) is reported. Approximately 80% of the grains present the standard texture of wrought Mg alloys while the grain orientation is rotated by ≈ 90º perpendicularly to the c axis in the remaining 20%. The deformation mechanisms responsible for this behavior are analyzed on samples deformed in tension and compression up to different strains. Compressive deformation of the grains with the standard texture is accommodated by 〈a〉 basal slip and extension twinning while tensile deformation promotes 〈a〉 basal and non-basal 〈a〉 prismatic and 〈a〉 pyramidal slip, leading to the typical yield asymmetry. However, the rotated grains present the opposite (and much stronger) yield asymmetry because tensile deformation is absorbed by 〈a〉 basal slip and extension twinning while compression deformation requires 〈a〉 basal slip and compression twinning. Thus, the contribution of the 20% rotated grains to the overall mechanical behavior leads to (almost) similar values of the yield strength in tension and compression. This work provides a physical understanding of the deformation behavior of dual-textured Mg alloys, that can be used to develop novel dual-textured Mg alloys with limited yield asymmetry. Graphical abstract: Image, graphical abstract